Implementasi Pelaksanaan Pendidikan Inklusi di Sekolah Reguler Kota Bandung - Madyaning Ratri, Titis; Nenden Ineu Herawati (Universitas Muhammadiyah Kuningan, 2024)
Education is the basic right of every Indonesian citizen, including those with special needs. The existence of inclusive education services is an education delivery system that provides services and opportunities for all children, including children with special needs and children with special intelligence or talent potential, to participate in education and learning in one environment together with children with general criteria. This research examines and describes the implementation of inclusive education implementation in a regular school in Bandung City, namely SDN 029 Cilengkrang Bandung City with 23 inclusive student participants. This research uses a descriptive - qualitative method, through a case study approach. The results of the research conducted are that in fulfilling the learning needs of students, an inclusive education programme is needed, namely an education system that provides opportunities for students with special needs to take part in learning in the same educational environment as other normal students. In running the inclusive education programme, of course, it is not as easy as turning your hand, it requires joint commitment and collaboration between school residents as well as related agencies in order to create a meaningful, comfortable, and certainly enjoyable learning environment for students with special needs.